Microbiome Fingerprint as Biomarker for Geographical Origin and Heredity in Crocus sativus: A Feasibility Study - Bhagat, Nancy; Sharma, Shivali; Ambardar, Sheetal; Raj, Sushmeeta; Trakroo, Deepika; Horacek, Micha; Zouagui, Rahma; Sbabou, Laila; Vakhlu, Jyoti (Frontiers in Sustainable Food Systems, 2021)
Host–microbiome interactions are specific and not random, making them defining entities for the host. The hypothesis proposed by various researchers earlier, that both plants and animals harbor specific inheritable core microbiome, is being augmented in the present study. Additionally, a case for using microbial fingerprint as a biomarker, not only for plant identification but also as a geographical indicator, has been investigated, taking Crocus sativus, saffron, as a study material. Crocus sativus, a monogenetic herb, on account of its male sterility and vegetative propagation, is reported to lack genome based molecular markers. Cormosphere microbiome (microbiome associated with corm) has been compared across three geographical locations, in two continents, to identify the core and unique microbiome, during the vegetative phase of its growth. Microbiome analysis done at phylum and genus level, using next generation sequencing technology, revealed that cormosphere at three locations harbored common phyla. At genus level, 24 genera were found common to all three geographical locations, indicating them to be part of the core microbiome of saffron. However, there were some bacterial genera unique to Kashmir, Kishtwar, and Morocco that can be used to develop microbial markers/geographical indicators for saffron grown in these regions. This is a preliminary study, indicating that the location specific bacterial community can be used to develop microbial barcodes but needs further augmentation with high coverage data from other saffron growing geographical regions.